Evolución de la Población Penal en Chile desde 1991 a 2007: aproximación empírica a los efectos de la reforma procesal penal = Penal Population Trends in Chile from 1991 to 2007 : an Empirical Approach to the Effects of the Chilean Criminal Procedure Reform - Arriagada, Isabel (Política criminal, 2021)
Criminal justice reform (RPP), implemented in Chile since 2000, constitutes the largest reform in the history of the Chilean criminal procedure. The present study uses a statistical linear regression model to assess the evolution of penal trends and the impact of the implementation of the RPP for the period 1991-2007 through comprehensive data by region, year, and procedural regime, while controlling for regional demographic growth. Findings reveal a sustained upward trend in the convicted prison population that originates in the 1990s, prior to the RPP. In addition, the reform caused a significant decrease in the prison population subjected to pre-trial custody. There is no evidence to suggest that the reform caused an increase in the convicted prison population during the study period. The effects of the reform on alternatives to imprisonment and parole are disparate. These findings provide sufficient evidence to confirm current hypotheses regarding punitive historical trends in Chile and the rights-based effects of the criminal justice reform.